CDC's Early Response to a Novel Viral Disease, Middle East Respiratory Syndrome Coronavirus (MERS-CoV), September 2012–May 2014. (July 2015) - Williams, Holly Ann; Dunville, Richard L.; Gerber, Susan I.; Erdman, Dean D.; Pesik, Nicki; Kuhar, David; Mason, Karen A.; Haynes, Lia; Rotz, Lisa; St. Pierre, Jeanette; Poser, Sarah; Bunga, Sudhir; et al.
The first ever case of Middle East Respiratory Syndrome Coronavirus (MERS-CoV) was reported in September 2012. This report describes the approaches taken by CDC, in collaboration with the World Health Organization (WHO) and other partners, to respond to this novel virus, and outlines the agency responses prior to the first case appearing in the United States in May 2014. During this time, CDC's response integrated multiple disciplines and was divided into three distinct phases: before, during, and after the initial activation of its Emergency Operations Center. CDC's response to MERS-CoV required a large effort, deploying at least 353 staff members who worked in the areas of surveillance, laboratory capacity, infection control guidance, and travelers' health. This response built on CDC's experience with previous outbreaks of other pathogens and provided useful lessons for future emerging threats.